The effect of e-wom and brand image towards Sushi Masa consumer purchasing decision - Nur Aiman Ikhwan Kamil; Albert Albert (Journal of Social Studies (JSS), 2020)
This digital age, people are using digital technology to facilitate all kinds of activities. Sushi Masa Jakarta, uses Zomato as one of their media as an E-WOM facility for consumers to express their feelings. In addition, the Authentic Sushi Image cannot be separated from Sushi Masa. The purpose of this study is to find out whether there is effects of E-WOM and Authentic Brand Image towards consumer purchasing decisions, partially and simultaneously. The theory used is Stimulus Response, supported by other marketing communication concepts. The method used is quantitative based on positive paradigm, considers the social reality can be proven scientifically. Data collection used were questionnaires with Likert scale. The results found the effect of E-WOM and Brand Image together towards consumer purchasing decisions by 62.9%. The author suggest that Sushi Masa can maintain E-WOM and Brand Image that has been built so that consumers continue to making purchasing decisions.